2023
DOI: 10.21037/jtd-22-1776
|View full text |Cite
|
Sign up to set email alerts
|

Cough in chronic lung disease: a state of the art review

Barnaby Hirons,
Katherine Rhatigan,
Harini Kesavan
et al.

Abstract: Chronic cough (CC; ≥8 weeks in duration) is a common and burdensome feature of respiratory diseases. The understanding of cough has progressed significantly in recent years, albeit largely in refractory (unexplained) chronic cough (RCC) in the absence of other respiratory conditions. The prevalence of CC in respiratory diseases is poorly described, but estimates have been reported: asthma (8–58%), chronic obstructive pulmonary disease (COPD; 10–74%), bronchiectasis (82–98%), interstitial lung disease (ILD; 50–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 124 publications
0
5
0
1
Order By: Relevance
“…Prior observational studies have noted epidemiologic connections between esophageal carcinoma and chronic respiratory illnesses including COPD, IPF, and asthma, suggesting potential shared environmental or behavioral factors 34 - 38 . For example, several large cohort studies found a significantly heightened risk of esophageal cancer among COPD patients compared to controls without airflow obstruction 5 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior observational studies have noted epidemiologic connections between esophageal carcinoma and chronic respiratory illnesses including COPD, IPF, and asthma, suggesting potential shared environmental or behavioral factors 34 - 38 . For example, several large cohort studies found a significantly heightened risk of esophageal cancer among COPD patients compared to controls without airflow obstruction 5 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in these patients the effectiveness of therapy with novel antitussive drugs such as P2X3 antagonists has not been proved yet. Instead, the results of this study are good premises to treat patients (especially COPD patients) with productive chronic cough more intensely with mucolytics, antibiotics or bronchodilators [ 3 , 24 26 ]. We have an existing therapy, azithromycin, which has been shown in several studies to reduce exacerbation rates, and it is recommended in the ERS and CHEST cough guidelines [ 3 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin has also been tested for other chronic cough-related diseases beyond COPD, e.g. in sarcoidosis cough, idiopathic pulmonary fibrosis cough and asthmatic cough, but with differing results [ 24 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Необходимо помнить, что причины длительного, хронического кашля различны для взрослых и детей [9][10][11]. Длительный кашель у ребенка в сочетании с другими дополнительными симптомами (одышка при физической нагрузке, гнойная мокрота, рецидивирующее свистящее дыхание, дефицит массы тела, задержка роста, быстрая утомляемость, стеаторея, деформация грудной клетки) всегда является признаком развития серьезного хронического заболевания бронхолегочной системы [12][13][14].…”
Section: Bronchopulmonology Otorhinolaryngologyunclassified